Transitional Support for Adults With Severe Mental Illness: Critical Time Intervention and Its Roots in Assertive Community Treatment. (September 2014) - Herman, Daniel B.
Professional social workers and other mental health providers have for many years been involved in delivering treatment and support services focused on the needs of adults with severe mental illnesses living in the community. While some models have evolved largely through practice experience, others have developed through research paradigms in which program developers have attempted to systematically test their models by employing randomized trials and other rigorous approaches to assess impacts. Critical time intervention (CTI) is a time-limited care coordination model intended to prevent homelessness and other adverse outcomes among adults with severe mental illness during periods of transition. After briefly tracing its roots in assertive community treatment—a pioneering earlier model of community care—this article describes CTI, the evidence for its effectiveness, preliminary efforts toward its broad dissemination, and offers thoughts about its further development and potential for adaptation.